PENGARUH PENERAPAN MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 4 PADANG - Fauzul Azmi (Jurnal Edukasi dan Penelitian Matematika, 2021)
One of the objectives from learning mathematics which is expected to develop optimally in students is mathematical problem solving skills. But in reality, so many students are still not capable to solve the mathematical problem. This also can  be seen in class VIII 1 of SMP Negeri 4 Padang. One of the reasons is because the learning methods that was used in schools has not been able to fully facilitate students’s mathematical problem solving skills development. Applying discovery learning model is a way to help developing student’s said skills. This study was to determine which one was better in developing such skill; those who learn with discovery learning or those who learn with direct learning model. This quasi-experiment study use randomized control group only design with all 8th grade students as the population and class VIII 1 A and VIII 2 B as the samples. A test done in the form of essay questions was used as the research instrument with a results of t-test showing P-value of 0.003, which was found at  = 0,05. Because P-value is lower ,  H0 was rejected and thus concluded that students whose learning used the discovery learning models has a better mathematical problem solving skill compare to students whose learning used direct learning model in 8th grade of SMP Negeri 4 Padang.